Pembelajaran bahasa Arab sebagai determinan keberhasilan tahfidz Al-Qur’an dalam pendidikan Islam: Arabic language learning as a determinant of Qur’an memorization success in Islamic education - Sulastri, Anti; Nurpriatna, Ade; Marwiji, Muh. Hasan (Sekolah Tinggi Agama Islam Kharisma Cicurug Sukabumi, 2025)
This study addresses the crucial relationship between Arabic language acquisition and Qur'an memorization in Islamic educational settings. The research aims to quantitatively measure the influence of Arabic language learning on Qur'an memorization ability among eighth-grade students at MTs Al-Ma'arij Bojonggenteng Sukabumi. Using a descriptive-correlational quantitative approach with total sampling of 28 students, data were collected through questionnaires and analyzed using statistical methods. The results demonstrate significant positive correlations, with 100% of students showing Arabic material comprehension, 100% achieving fluent Arabic vocabulary pronunciation, and 92.85% mastering proper Arabic intonation. The study concludes that Arabic language proficiency substantially enhances Qur'an memorization capabilities through improved semantic understanding and phonetic accuracy. These findings imply the necessity of developing integrated curricula that combine linguistic and spiritual approaches in Islamic education, suggesting that Arabic language instruction should be systematically aligned with Qur'anic studies to optimize memorization outcomes. The research contributes to the development of more effective pedagogical models in religious education that leverage linguistic competence for enhanced spiritual learning.